An Academic Representation of the Use of Search-and-Rescue (SAR) Robots in Post-Earthquake Japan as Depicted in the Anime Tokyo Magnitude 8.0 - Bustari, Ahdian Azri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Research with the aim of analyzing the representation of the use of SAR robots after the earthquake disaster in Japan in the anime Tokyo Magnitude 8.0 has been conducted. This research uses a descriptive qualitative approach with Peirce's semiotic analysis method. The results show that there are seven scenes in the anime Tokyo Magnitude 8.0 that contain two types of robots, namely Resukyū Robō and Semi-autonomous Robot. Specifically, three of the seven scenes depict the direct representation of the use of SAR robots after the earthquake disaster in Japan as search and rescue robots for evacuating victims. Meanwhile, the other four scenes are supporting scenes that also discuss SAR robots. Further analysis shows that Resukyū Robō is used as a rescue robot, while Semi-autonomous Robot is used more as a search robot. Although they have different functions, these two types of robots support each other in the evacuation of victims after a disaster.